Enhanced efficiency and stability of triple‐cation perovskite solar cells with CsPbIxBr3 − x QDs "surface patches". Issue 3 (2nd February 2022) - Yang, Guang; Zhang, Hengkai; Li, Siqi; Ren, Zhiwei; Fang, Guojia; Lei, Dangyuan; Li, Gang
Abstract: Perovskite solar cells (PSCs) with a light‐harvesting three‐dimensional perovskite bulk layer as backbone component have achieved great progress in performance. Nonradiative recombination is one major place to improve efficiency and stability as they cause significant energy loss in PSCs. Additionally, an imperfection in grain boundaries will initiate device degradation. One of the most successful strategies to decrease nonradiative recombination in PSCs is the introduction of reduced dimensional perovskite (e.g., perovskite quantum wells), benefiting the device's efficiency and stability tremendously. Here, instead of quantum wells, mixed‐cation perovskites with ligand‐contained CsPbBr x I3 − x quantum dots (QDs) are prepared, which is shown to function as perovskite healing "surface patches." Benefiting from the "surface patches" effect, the QDs‐film shows reduced defects and enhancing film quality which lead to the excellent performance of solar cells (enhancing the power conversion efficiency from 19.21% of the control device to 21.71% [22.1% in reverse scan]). Abstract : Perovskite‐healing "surface patches" are developed by ligand‐contained CsPbI x Br3 − x quantum dots (QDs). Benefiting from the "surface patches" effect, the QDs‐film shows reduced defects and enhancing film quality which lead to the excellent performance of the solar cell.